Inactivation of Nocardiophages φC and φEC by Extracts of Bacteriophage-Attachable Cells - Brownell, George H. (1971)
Cultures of several species of Nocardia, including N. erythropolis Mat-Ce and Mat-cE mating strains, were extracted with solvents in an attempt to isolate an inactivating complex for nocardiophages φC and φEC. Ethanol was the only solvent found effective in solubilizing an inhibitory substance. Inactivating extracts were obtained from the cells of all species to which the phage were able to attach. After extraction of whole cells or cell wall preparations, the phage could not effectively attach to them. Both phages φC and φEC were inactivated by the same complex. However, phage φEC inactivation was 10-fold greater than φC inactivation. The velocity of inactivation was about 4.1 × 10(2) plaque-forming units per microgram per minute for φC and 1.1 × 10(3) plaque-forming units per microgram per minute for phage φEC. The cell extracts required divalent cations for phage inactivation. The inhibitory capacity of the cell extracts was reduced or lost by the activity of proteolytic enzymes, Tween 80, 2-mercaptoethanol, thymol, and sodium lauryl sulfate. Boiling the extract for 10 min did not alter its activity. The inactivating substance was postulated to be a lipoprotein of considerable complexity, unique in the ease with which it is solubilized from host cells by ethanol.